The Feasibility of Developing a Construction Material From Basaltic Quarry Waste and Recycled High-Density Polyethylene - Johnson Ngugi; George O. Rading; Thomas O. Mbuya (The Scientific World Journal)
Quarry waste is a fine rock aggregate produced as a by-product of the rock-crushing process in quarries which is environmentally hazardous when poorly disposed. This paper presents the results of a study carried out to explore the feasibility of recycling basaltic quarry waste (BQW) with waste high-density polyethylene (HDPE) into sustainable construction materials. Recycled HDPE/BQW formulations were melt-mixed in a single-screw extruder and then transfer-moulded into experimental samples. No significant chemical transformations were detected by Fourier transform infrared spectroscopy. Thermogravimetric analyses showed an improvement in the thermal stability of HDPE with the addition of BQW. Scanning electron microscopy imaging revealed generally poor adhesion between the two phases. Both tensile and impact strength initially increased but decreased at higher filler loading. However, stiffness, compressive strength, compressive modulus, density, and hardness improved with filler content for all particle sizes. The increase in water absorption with increasing filler content was not significant. This study demonstrates that BQW is a suitable filler for HDPE and the resulting material may be used to make roofing tiles and paving blocks.